Efficiency in Italian Commercial Banks: A Stochastic Frontier Analysis - Cheng, Youwen (2019)
Finance is an important support for social and economic development. As the core industry of the financial system, the banking industry's steady development is related to the country's financial stability and economic security. Among them, the high efficiency of commercial banks, to some extent, reflects the contribution rate to economic development. Therefore, studying the efficiency of commercial banks is of great significance to the steady development of the national banking industry.